PENGARUH KARAKTERISTIK PERSONAL AUDITOR TERHADAP TINGKAT PENERIMAAN AUDITOR ATAS PENYIMPANGAN PERILAKU DALAM AUDIT - Angkoso, Annabela; Handoko, Jesica; Harimurti, Yohanes (Jurnal Akuntansi Kontemporer, 2013)
The cornerstone of the auditing process in the form of audit results. The audit results will be made to produce a final decision is referred to the audit judgment. An auditor to generate audit judgment will also be influenced by several factors such as gender, obedience pressure, task complexity, experience of audit and audit expertise. On the research conducted, aimed to analyze the influ-ence of gender, obedience pressure, task complexity, audit experience and expertise of an auditor in the audit of the audit judgment result of the audit. This study uses the respondent auditor who worked in Public Accounting Firm IPAI listed on the website in 2012 using questionnaires as much as 91 questionnaire as a research object. From research conducted shows that obedience pres-sure, task complexity, skills audit has an influence on by an auditor in public accounting firm in Surabaya, while gender, experi-ence shows audit results had no influence on by an auditor who works in the Office of the Public Accountant in Surabaya audit judgment.